2019
DOI: 10.1029/2019gl084675
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt Bølling‐Allerød Warming Simulated under Gradual Forcing of the Last Deglaciation

Abstract: During the last deglaciation, a major global warming trend was punctuated by abrupt climate changes, likely related to Atlantic meridional overturning circulation (AMOC). One problem is that an abrupt increase in the AMOC during the Bølling-Allerød (BA) transition occurred when the melting of Northern Hemisphere ice sheets was significant, which tended to weaken the AMOC. Here, from transient simulations of the last deglaciation using an atmosphere-ocean general circulation model, we show that an abrupt increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 66 publications
4
71
0
2
Order By: Relevance
“…In the present study, the experiments have been carried out with the coupled atmosphere-ocean general circulation model, MIROC4m, a mid-resolution model developed jointly by the Center for Climate System Research (CCSR), National Institute for Environmental Studies (NIES) and Frontier Research Center for Global Change (FRCGC), in Japan (K-1 model developers, 2004). This model has previously been used to study a variety of climate states, for example, future RCP4.5 and RCP8.5 scenarios (Bakker et al, 2016), the mid-Holocene (Ohgaito et al, 2013), the Last Glacial Maximum (Yanase and Abe-Ouchi, 2007), and the mPWP (Chan et al, 2011). The same model with a higher resolution was included in the Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC, 2013).…”
Section: Model Descriptionmentioning
confidence: 99%
“…In the present study, the experiments have been carried out with the coupled atmosphere-ocean general circulation model, MIROC4m, a mid-resolution model developed jointly by the Center for Climate System Research (CCSR), National Institute for Environmental Studies (NIES) and Frontier Research Center for Global Change (FRCGC), in Japan (K-1 model developers, 2004). This model has previously been used to study a variety of climate states, for example, future RCP4.5 and RCP8.5 scenarios (Bakker et al, 2016), the mid-Holocene (Ohgaito et al, 2013), the Last Glacial Maximum (Yanase and Abe-Ouchi, 2007), and the mPWP (Chan et al, 2011). The same model with a higher resolution was included in the Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC, 2013).…”
Section: Model Descriptionmentioning
confidence: 99%
“…It was driven by the collapse of vulnerable ice sheet sectors, and was concurrent with rapid Northern Hemispheric warming and disruptions in oceanic and atmospheric circulation 3 , 4 . The ice-ocean-climate feedbacks operating during this period are not well understood largely due to a lack of consensus on the sources of MWP-1A 5 , 6 , which, in turn, were likely to be a key driver in stimulating rapid deglacial climate change 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies show a strengthening of the AMOC in response to the expansion of the northern glacial ice sheet (Eisenman et al, 2009;Brady et al, 2013;Zhang et al, 2014a;Gong et al, 2015;Klockmann et al, 2016;Brown and Galbraith, 2016;Kawamura et al, 2017), whereas one study shows a reduction of the AMOC (Kim, 2004). From sensitivity experiments, it is clearly shown that the higher Northern American glacial ice sheets enhance the surface wind as well as the wind-driven oceanic transport of salt into the deep-water formation region over the North Atlantic, which increases the surface salinity and causes a strengthening of the AMOC (Oka et al, 2012;Muglia and Schmittner, 2015;Sherriff-Tadano et al, 2018). Other studies also suggest the importance of changes in surface cooling (Smith and Gregory, 2012), which can cause either a strengthening of the AMOC by enhancing deep-water formation over the North Atlantic (Schmittner et al, 2002;Oka et al, 2012;Smith and Gregory, 2012) or a weakening of the AMOC by increasing the amount of sea ice over the northern North Atlantic and Southern Ocean (Kawamura et al, 2017).…”
Section: Introductionmentioning
confidence: 99%